Functionalization of Zr-based MOFs with alkyl and perfluoroalkyl groups: the effect on the water sorption behavior. Issue 45 (16th October 2015) - Yu, C.; Bourrelly, S.; Martineau, C.; Saidi, F.; Bloch, E.; Lavrard, H.; Taulelle, F.; Horcajada, P.; Serre, C.; Llewellyn, P. L.; Magnier, E.; Devic, T.
Abstract : The influence of organic functional groups (fluorinated versus non-fluorinated) on the hydrophilic/hydrophobic balance of MOFs has been studied. Abstract : Stability and sorption of Metal–Organic Frameworks (MOFs) towards water are critical in many applications, and can a priori be modulated through the introduction of suitable organic functional groups on their backbone. We report here the preparation of a series of Zr(iv )-based MOFs functionalized with alkyl and perfluoroalkyl groups and their characterization by X-ray powder diffraction, multi-nuclei ( 1 H, 13 C, 19 F) solid state nuclear magnetic resonance analyses, and nitrogen sorption measurements at 77 K. Their water sorption behavior was evaluated at 298 K and related to their physico-chemical features, highlighting both the effect of the confinement and the nature of the functional groups on the hydrophilic/hydrophobic balance.